상기생 물추출물이 대식세포 활성화와 Th1 반응에 미치는 효과 - 신혜영(Hye Young Shin); 장문희(Wen Ji Zhang); 김윤철(Youn Chul Kim); 윤용갑(Yong Gab Yun); 박현(Hyun Park) (동의생리병리학회지, 2008)
In the recently, increased concern has been focused on the pharmacology and clinical utility of herbal extracts and derivatives as a drug or adjunct to chemotherapy and immunotherapy. Here we investigated the effect of the water extract of Loranthi Ramulus (LR) in production of inflammatory mediators and expression of toll-like receptor (TLR)-4, CD14 from peritoneal macrophage. We assayed the effect of LR water extract in cell proliferation in vitro and Th1/Th2 cytokine level in vivo. In peritoneal macrophages, water extract of LR water extract increased the production of Nitric oxide (NO) and $TNF-α$. Also, LR water extract increased Con A-induced cell proliferation and IgG1, IgG2a level in serum. However, i.p. injection of water extract of LR water extract did not affect the level of $TNF-α$, $IFN-γ$, IL-2, IL-4 and IL-5 in serum of mice. These studies indicate that LR water extract induces macrophage activation and suggest the possible use of LR water extract in macrophage-based immunotherapies.